Estudo dos efeitos do inibidor de recaptação de serotonina citalopram no processamento auditivo central em idosos - Polanski, José Fernando [UNIFESP] (2016)
Objective: The central auditory processing disorders are related to difficulties in processing sound information at the level of central auditory pathways. It is known that in these pathways, the presence of the neuromodulator serotonin is abundant and it is related to the proper functioning of these brain structures. The objective of this research was to evaluate the effects of therapy with citalopram, a selective inhibitor of serotonin reuptake, on the central auditory processing in the elderly measured by central auditory tests. Secondly, assess the effects of medication on the self-perception of hearing loss and tinnitus, when present, through quality of life questionnaires. Method: prospective study, randomized, double-blind, placebo-controlled (registry number ACTRN12614000570684). Subjects were 60 years or older with normal hearing thresholds or symmetrical sensorineural hearing loss up to 70 dBHL, wordrecognition score equal to or better than 70%, and diagnosed with central auditory processing disorders. They underwent the mini-mental state examination, as a way to screen those with the possibility of dementia; they also underwent the Beck depression inventory, for screening individuals with depression. The 49 selected subjects were randomly divided into two groups: one received citalopram 20mg / day and the other placebo for 6 months. The central auditory tests were applied to the selection of individuals with auditory processing disorders and repeated after treatment. The tests were: sound localization, speech in noise, dichotic digits test, pitch pattern sequence, duration pattern test and gaps-in-noise. We also applied the hearing handicap inventory for the elderly and the tinnitus handicap inventory for those with tinnitus. Results: Comparisons of central auditory tests pre - and posttreatment in groups showed: sound localization (p=0,735), pitch pattern sequence humming (p=0,102), pitch pattern sequence nomination (p=0,157) duration pattern test humming (p=0,102), duration pattern test nomination (p=0,196) and gaps-in-noise (p=0,683). Dichotic tests in right and left ear, respectively: speech in noise (p=0,143; p=0,052), dichotic digits test (p=0,492; p=0,233). Hearing handicap inventory for the elderly (p=0,169) and the tinnitus handicap inventory (p=0,501). Conclusion: there was no statistically significant effect with the use of citalopram in central auditory processing tests of the subjects. The quality of life questionnaires related to the impact of hearing loss and tinnitus did not show a statistically significant change with the use of medication.